Space Junk - Hanshaw, Julian, 1971- (Tops Shelf Productions, an imprint of IDW publishing, a division of Idea and Design Works, LLC, 2024)
Faith has a metallic mystery bolted to her head. Hoshi keeps his rage in check with an emotional support chicken. On a dying world where most adults have already left and the remaining kids are training for their turn, these two are starting to wonder "what's the point?" Gradually, a cluster of lonely souls who've spent their lives emotionally adrift are pulled into one another's orbits as they try to stay in place in a universe that is moving all too quickly.